Paisagem Cultural: desafios na construção e gestão de uma nova categoria de bem patrimonial. - Costa, Luciana de Castro Neves (2018)
Cultural Landscape category is part of cultural heritage understanding expansion movement, understood as a spatial section representative of the interaction between society and the environment process, based on its features and the values attributed to it. Based on this generic concept, this research aims to analyze the process Cultural Landscape category construction, both by UNESCO and IPHAN, focusing on dialogical relations that such comprehension proposes to an articulation between natural and cultural, as well as on the values that guide this patrimonial property typology selection and management. It is also sought to understand its fulfillment as a preservation tool, based on Testo Alto (Pomerode) and Rio da Luz (Jaraguá do Sul) case study, two rural integrated cores in Santa Catarina, the only Brazilian Cultural Landscape declared to date. Therefore, in this work it is used, as methodological support, bibliographical and documentary research and semistructured interviews. As results obtained through this research, we can perceive that, although this category allows the framing of patrimonial references not contemplated in preservation policies yet, based on a synthesis notion, some accomplishment’s difficulties still exist, such as the urban framework as Cultural Landscape, the landscape dynamism management as heritage, and, especially in Brazil, the complexity of the management tool adopted, constituted by shared management agreement.